Limonoids from fruits of Melia dubia cav. in Vietnam - Hieu, Tran Trung; Tuan, Nguyen Ngoc; Tien, Nguyen Quyet; Thanh, Nguyen Tan; Hoang, Vu Dinh; Trinh, Nguyen Thi Nu; Thang, Tran Dinh (Vietnam Journal of Science and Technology, 2021)
A phytochemical study on fruits of Melia dubia Cav. collected in Nghe An province led to the isolation of three secondary metabolites, including 21α-O-methylmelianodiol (1), 21β-O-methylmelianodiol (2) and (21S,23R,24R)-21,23-epoxy-24-hydroxy-21β-methoxytirucalla-7,25-dien-3-one (3). The chemical structures of these compounds were determined on the basis of 1D, 2D NMR, UV, IR and MS analytical results and comparison with reported data. All three compounds (1–3) were isolated from this plant for the first time